Ending over-lending: assessing systemic risk with debt to cash flow - Bruce A. Ramsay; Peter Sarlin (European Central Bank (ECB), 2015)
This paper introduces the ratio of debt to cash flow (D/CF) of nations and their economic sectors to macroprudential analysis, particularly as an indicator of systemic risk and vulnerabilities. While leverage is oftentimes linked to the vulnerability of a nation, the stock of total debt and the flow of gross savings is a less explored measure. Cash flows certainly have a well-known connection to corporations' ability to service debt. This paper investigates whether the D/CF provides a means for understanding systemic risks. For a panel of 33 nations, we explore historic D/CF trends, and apply the same procedure to economic sectors. In terms of an early-warning indicator, we show that the D/CF ratio provides a useful additional measure of vulnerability to systemic banking and sovereign crises, relative to more conventional indicators. As a conceptual framework, the assessment of financial stability is arranged for presentation within four vulnerability zones, and exemplified with a number of illustrative case studies.
Keywords: E21; F34; G01; H63; 330; debt to cash flow; early-warning indicator; systemic risk; total debt to gross savings